Sources of borrowing and fiscal multipliers - Romanos Priftis; Srecko Zimic (European Central Bank (ECB), 2018)
This paper finds that debt-financed fiscal multipliers vary depending on the location of the debt buyer. In a sample of 33 countries fiscal multipliers are larger when government purchases are financed by issuing debt to foreign investors (non-residents), compared to when they are financed by issuing debt to home investors (residents). In a theoretical model, the location of the government creditor produces these differential responses through the extent that private investment is crowded out. International capital mobility of the resident private sector decreases the difference between the two types of financing both in the model and in the data.
Keywords: E62; F41; H3; 330; Fiscal multipliers; structural vector autoregressions; sign restrictions; proxy-SVAR; investment crowding in; debt financing; small open-economy model